2022
DOI: 10.3390/jcm11061480
|View full text |Cite
|
Sign up to set email alerts
|

Polychromatic Assessment of a Refractive Segmented EDOF Intraocular Lens

Abstract: This study aimed to evaluate in vitro performance refractive segmented EDOF intraocular lenses under polychromatic light using an optical bench that complies with the ISO 11979-2 Norm. The through focus modulation transfer function (TF-MTF) of the Femtis Comfort LS-313 MF15 (Oculentis GmbH, Berlin, Germany) IOL was evaluated for IOLs with three different base powers. The effect of the asymmetry of the segmented designs was evaluated with 3 different wavelengths and with polychromatic light at a 3.0 mm and 5.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In clinical studies, the Oculentis +1.50 provided excellent distance and intermediate vision, but near vision was not enough for reading small prints. Contrast sensitivity was high, with very low incidences of photic phenomena and a high level of patient satisfaction 65,66. In vitro performance of the lens under polychromatic light demonstrated that additionally to the low add value, the segmented bifocal design gives the lens its EDOF character 66…”
Section: Evidence About the Clinical Behavior Of Edof Iolsmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical studies, the Oculentis +1.50 provided excellent distance and intermediate vision, but near vision was not enough for reading small prints. Contrast sensitivity was high, with very low incidences of photic phenomena and a high level of patient satisfaction 65,66. In vitro performance of the lens under polychromatic light demonstrated that additionally to the low add value, the segmented bifocal design gives the lens its EDOF character 66…”
Section: Evidence About the Clinical Behavior Of Edof Iolsmentioning
confidence: 99%
“…Contrast sensitivity was high, with very low incidences of photic phenomena and a high level of patient satisfaction. 65,66 In vitro performance of the lens under polychromatic light demonstrated that additionally to the low add value, the segmented bifocal design gives the lens its EDOF character. 66 (2) Acunex Vario AN6 V (Teleon Surgical): The Acunex Vario AN6 V lens is a foldable single-piece IOL for EDOF and high-contrast sensitivity with aspherical surface and blue light filter (Fig.…”
Section: Type 3-mf With Low-power Near-vision Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we assessed the optical performance of this lens in vitro using an optical bench under polychromatic light. Our findings demonstrated that the through-focus modulation transfer function (TF-MTF) curves (at 50 cycles/mm) displayed a bifocal profile, effectively creating an EDoF design in practical terms [20].…”
Section: Multifocal Intraocular Lensmentioning
confidence: 86%
“…The diffractive profile of these IOLs exhibits distinct efficiency levels for each wavelength. By combining foci with varying efficiencies, these lenses create an extended focal point for enhanced light distribution [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%